Cement supply chain distortion and its Shadow Market in Ethiopia - Alemayehu Derege (International Journal of Industrial Engineering and Production Research)
The booming of construction sector, including cement factories, has been great success, however, the price of cement has been quadrupled. Among others, critical shortage of cement is observed throughout the country regardless of the success, demanding a critical investigation into its supply chain, governance and regulatory system. Mixed, qualitative and quantitative approaches are applied to investigate the value chain, its administration and regulatory framework. SEM was used to index the level of cement supply distortions in the country.  Samples are taken through referral technique from stratified target group across Ethiopian cement supply chain, starting from factory CEO to end-users, from purposively selected major factories. Multinomial logit model is used to analyze the determinant of cement supply distortion. The study found mis-management of regulation, high intervention with ineffective regulatory measure, opened up a room for bribery, favoritism, government interventionism and amplified the roles of intermediaries beyond the market requirement. Brokers are involved in about 85 percent of the country's total cement distribution. Besides, not only intermediaries but also the factories and their agents are contributing a lot in cement supply distortion. The supply chain distortion is observed in all market types, black, gray, and white respectively. The regulatory framework is ineffective and few regulatory bodies are fixed towards reactive measures. Majority of cement distribution is facilitated by brokers and factory agent. Hoarding and smuggling emerge as the most influential factors, with their increase being strongly and significantly linked to a rise in high and severe illegal cement distribution. Regulatory strength and administrative malpractice display complex patterns, indicating that having policies in place is not sufficient; effective enforcement is crucial. Strengthening regulatory, good governance and law enforcement system reduces the cement supply distortion while long run digitalization should be targeted along with supply side intervention.